Death in a Dry River: Black Life, White Property, Parched Justice - Perera, Suvendrini (Edinburgh University Press, 2011)
This essay deals with the sentence handed down in April 2010 on the death of the 33 year-old Kumantaye Ryder in the dry creek bed of the Todd River in Alice Springs, Central Australia. The riverbed, we argue, is a racially marked and politically charged location that plays an historical and continuing role in defining relations between settler and colonized. We situate our analysis of this site in a context where autonomy over and access to land, and the significance of remote townships and town camps, are bitterly contested as part of a wider clash over Aboriginal subjectivities, citizenships and futures. Drawing on Cheryl Harris's critical insights (1993) into how in the United States ‘rights in property are contingent on, intertwined with, and conflated with race’, we examine the sentencing of the accused in the death of Kumantaye Ryder against the multiple meanings of property. We conclude our analysis by underscoring the manner in which racialised formations of law and property work to secure, entitle and affirm the very possibility of life and future itself.